2013
DOI: 10.3126/jnps.v32i3.6682
|View full text |Cite
|
Sign up to set email alerts
|

Enteric fever in Children at Dhulikhel Hospital

Abstract: Introduction: Typhoid fever is one of the most common public health problems in Nepal. It occurs in all parts of the world where water supplies and sanitation are sub-standard. In Dhulikhel hospital, this is one of the top acute febrile illnesses in inpatient department. The objectives of this study were to evaluate the clinical and laboratory parameters including culture and sensitivity, the response to therapy, and complications of enteric fever among child cases at Dhulikhel Hospital. . Statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
14
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 13 publications
17
14
3
Order By: Relevance
“…This is similar to the observations by Chandrasekhar et al, 1 Gupta et al, 3 Jog et al, 4 Chowta et al, 15 Singh et al 16 and Malla et al 17 studies.…”
Section: Investigations/ Blood C and S Patternsupporting
confidence: 82%
See 1 more Smart Citation
“…This is similar to the observations by Chandrasekhar et al, 1 Gupta et al, 3 Jog et al, 4 Chowta et al, 15 Singh et al 16 and Malla et al 17 studies.…”
Section: Investigations/ Blood C and S Patternsupporting
confidence: 82%
“…Majority of the study population were from upper middle class 58.82% (30), whereas lower middle class contributes 31.37% (16) and hardly few cases were noticed in upper class and upper-lower class i.e. 5.88% (3) and 3.92% (2) respectively.…”
Section: Figure 1 Number Of Target Population and Study Populationmentioning
confidence: 99%
“…This demonstrates that ST and SPA are fully susceptible to ceftriaxone. These results are consistent with other studies from Nepal which have shown full susceptibility to ceftriaxone [14][15][16] . An important implication of these fi ndings is that ceftriaxone is a very good choice for empirical treatment of suspected enteric fever.…”
Section: Ceftriaxonesupporting
confidence: 83%
“…Other studies have also reported similar fi nding 14,15 . However, because of toxicity its use is limited.…”
Section: Gentamicinsupporting
confidence: 68%
“…Other large series include those by Chowta et al, S. jog et al and Walia et al 2,12,13 Most of the clinical symptoms and signs reported by us are similar to those reported earlier. [14][15][16] Children in this study commonly presented with fever, headache and gastrointestinal symptoms and diarrhea was more common than constipation. Our observation of fever as a common complaint in all the children and diarrhea being more common than constipation, similar findings were also observed by other author.…”
Section: Discussionmentioning
confidence: 99%